Peningkatan Hasil Belajar Pendidikan Agama Islam Siswa Melalui Media Pembelajaran Video di SDN 12 Kampung Sopan - Nora, Riska Efebri (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
The implementation of education is a shared responsibility between families, communities, and the government. In this context, schools serve as the center for teaching and learning activities, which are also the hope of parents, families, and society for educating the nation's future generations. Islamic Religious Education (PAI) plays an essential role in forming religious and responsible individuals. One way to improve learning quality is by utilizing creative learning media. This study aims to improve the learning outcomes of PAI students through the use of video learning media in class 5 of UPTD SDN 12 Kampung Sopan. This research employs the Classroom Action Research (CAR) approach to evaluate the impact of video media on students' learning outcomes. The results of this study are expected to contribute to efforts to improve the quality of PAI learning in schools.